Lead and antimony in basal ice from Col du Dome (French Alps) dated with radiocarbon: a record of pollution during antiquity - Preunkert, Susanne; McConnell, Joseph R.; Hoffmann, Helene (Geophysical research letters, 2019)
Lead and antimony measurements in basal ice from the Col du Dome glacier document heavy metal pollution in western Europe associated with emissions from mining and smelting operations during European antiquity. Radiocarbon dating of the particulate organic carbon fraction in the ice suggests that the basal ice dates to 5,000 ± 600 cal years BP. In agreement with a precisely dated Greenland lead record, the Col du Dome record indicates two periods of significant lead pollution during the Roman period, that is, the last centuries before the Common Era to the second century of the Common Era. Atmospheric modeling and the Col du Dome record consistently show an overall magnitude of the lead perturbation 100 times larger than in the Greenland record. Antimony closely tracked lead, with antimony pollution about 2 orders of magnitude lower, consistent with European peat records.